TAFSĪR RŪḤ AL-MA‘ĀNĪ LI AL-ALŪSĪ WA BAYĀN AL-MUNĀSABĀT FĪ TAFSĪRIH - Zainul Arifin (Islam Futura, 2017)
Essentially, this book of tafseer is a comprehensive one since has interpretation in various aspects. All people from the East and the West can do so and have certainly will have a happy soul as he deepens the ocean of interpretation. An interpretation that gives you light of the world and religion so that you feel as if it has been opened to you the gates of heaven. It is the previously unpublished interpretation pattern. So no doubt that the author must be a researcher, interpreter, expert in Islamic jurispridence and Arabic, as well as a mufti of Baghdad. He is al-Alusi who revived the prestige of Baghdad in the aspects of civilization and knowledge. His interpretation is focused on the munasabat and unity of the theme with a stunning explanation so that we can enjoy the contents of this interpretation.